2009
DOI: 10.1097/mlr.0b013e3181923fd7
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Patient Satisfaction Surveys and Alternative Coding Procedures to Predict Malpractice Risk

Abstract: Findings suggest that minimum satisfaction score may provide a useful metric for identifying and prioritizing malpractice risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Each drop in minimum overall score along a five-step scale of "very good" to "very poor" corresponds to a 21.7 percent increase in the likelihood of being named in a suit. 29 Forty-six percent of malpractice risk is attributed to physician-specific characteristics, including patient experience. 29 Efforts to improve patient experience also result in greater employee satisfaction, reducing turnover.…”
Section: Why Is It Important To Measure Patient Experience?mentioning
confidence: 99%
See 1 more Smart Citation
“…Each drop in minimum overall score along a five-step scale of "very good" to "very poor" corresponds to a 21.7 percent increase in the likelihood of being named in a suit. 29 Forty-six percent of malpractice risk is attributed to physician-specific characteristics, including patient experience. 29 Efforts to improve patient experience also result in greater employee satisfaction, reducing turnover.…”
Section: Why Is It Important To Measure Patient Experience?mentioning
confidence: 99%
“…29 Forty-six percent of malpractice risk is attributed to physician-specific characteristics, including patient experience. 29 Efforts to improve patient experience also result in greater employee satisfaction, reducing turnover. Improving patients' experiences requires improving work processes and systems that enable clinicians and staff to provide effective care.…”
Section: Why Is It Important To Measure Patient Experience?mentioning
confidence: 99%
“…A direct correlation exists between physician behaviors such as poor communication that causes patient dissatisfaction and malpractice risk. [29][30][31][32] When physicians receive complaints of unprofessional behavior, communication concerns are among the most common. 33 …”
Section: Improving Patient Safety By Facilitating Information Transfementioning
confidence: 99%
“…Patient satisfaction is positively correlated with patient compliance, health outcomes, improvement in symptoms, perceptions of caregiver competence, reduced incidence of malpractice suits, and patient retention. [10,11] One study also suggests that hospital patient satisfaction is impacted specifically by four areas: hospital staff, patient care and treatment, information on leaving the hospital, and overall impression. [12] Finally, it has been shown that hospitals with higher patient satisfaction provide more efficient care and greater quality of care in surgery.…”
Section: Introductionmentioning
confidence: 99%